2016
DOI: 10.1002/cssc.201501637
|View full text |Cite
|
Sign up to set email alerts
|

Thickness‐ and Particle‐Size‐Dependent Electrochemical Reduction of Carbon Dioxide on Thin‐Layer Porous Silver Electrodes

Abstract: The electrochemical reduction of CO2 can not only convert it back into fuels, but is also an efficient manner to store forms of renewable energy. Catalysis with silver is a possible technology for CO2 reduction. We report that in the case of monolithic porous silver, the film thickness and primary particle size of the silver particles, which can be controlled by electrochemical growth/reduction of AgCl film on silver substrate, have a strong influence on the electrocatalytic activity towards CO2 reduction. A 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 33 publications
(36 reference statements)
1
37
0
Order By: Relevance
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
“…Clearly, tuning of nanocrystalline Ag electrocatalysts in terms of their geometrical parameters such as size and shape plays a significant role in the improvement of catalytic performance for selective ECR to CO. Indeed, the impact of both particle size and nanomorphology of Ag electrocatalysts has been widely reported for selective ECR to CO in literature …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
See 3 more Smart Citations